Simulation of rice blast epidemics under current and projected climate change scenarios - Callejo, Abel Melquiades; Mirni, Eka; Carvajal, Raphael; Ortega, Kendrix; Pangga, Ireneo; Castilla, Nancy (International Rice Research Institute, 2024)
Rice blast disease caused by Magnaporthe oryzae B.C. Couch causes significant yield losses in rice production globally. This research study was conducted develop, verify, and validate a mechanistic rice blast simulation model using STELLA 9.1 modeling software based on the structure of the EPIRICE model developed at IRRI. A leaf blast submodel was coupled to the neck blast submodel using the leaf and neck blast relationship based on a linear regression equation. The model was developed and verified using leaf and neck blast data from eight verification sites and validated in five sites in the Philippines. In general, graphical comparison showed similar shapes of simulated and observed leaf blast severity and neck blast incidence progress curves. Statistical validation of the model used the Wilcoxon test, Root mean square error (RMSE), and equivalence test. The RMSE test indicated satisfactory results, showing low values for leaf blast severity and approximately twice as high values for neck blast incidence. The Wilcoxon test showed significant differences between observed and simulated leaf blast severities at all validation sites and 60% accuracy in predicting neck blast. On the other hand, the equivalence test showed 40% accuracy in predicting leaf blast severity and 40% accuracy in predicting neck blast incidence. Inconsistencies in the statistical tests can be due to the complexity and differences in the leaf and neck blast pathosystems. Potential leaf blast epidemics were mapped in Bangladesh, India, Indonesia and the Philippines using projected weather data generated by the Australian Community Climate and Earth System Simulator (ACCESS) Coupled Model for the 6th Coupled Model Intercomparison Project (CMIP6) of International Panel for Climate under two climate scenarios. SSP2-4.5 (moderate greenhouse gas pathway) and SSP5- 8.5 (high greenhouse gas emission pathway) were used to evaluate the projected effects of climate change disease epidemics in 2030 and 2050. Projected leaf blast epidemics are expected to decline in several rice-growing regions. However, rice-growing areas with significant rainfall and cool temperature due to climate change remain at risk for the disease. This underscores the importance of prioritizing the development and implementation of strategies to manage leaf blast in vulnerable areas.